Bimanual motor skill learning after stroke: Combining robotics and anodal tDCS over the undamaged hemisphere: An exploratory study - De Laet, Chloë; Herman, Benoît; Riga, Audrey; Bihin, Benoît; Regnier, Maxime; Leeuwerck, Maria; Raymackers, Jean-Marc; Vandermeeren, Yves (Frontiers in Neurology, 2022)
Background. Because a stroke can impair bimanual activities, enhancing bimanual cooperation through motor skill learning may improve neurorehabilitation. Therefore, robotics and neuromodulation with transcranial direct current stimulation (tDCS) are promising approaches. To date, tDCS has failed to enhance bimanual motor control after stroke possibly because it was not integrating the hypothesis that the undamaged hemisphere becomes the major poststroke hub for bimanual control. Objective. We tested the following hypotheses. (I) In chronic hemiparetic stroke patients training on a robotic device, anodal tDCS applied over the primary motor cortex of the undamaged hemisphere enhances bimanual motor skill learning compared to sham tDCS. (II) The severity of impairment correlates with the effect of tDCS on bimanual motor skill learning. (III) Bimanual motor skill learning is less efficient in patients compared with healthy individuals (HI). Methods. Seventeen chronic hemiparetic stroke patients and seven healthy individuals learned a complex bimanual cooperation skill on the REAplan® neurorehabilitation robot. The Bimanual Speed/Accuracy Trade-Off (biSAT), Bimanual Coordination (biCo) and Bimanual force (biFOP) scores were computed for each performance. In patients, real/sham tDCS was applied in a crossover, randomized, double-blind approach. Results. Compared to sham, real tDCS did not enhance bimanual motor skill learning, retention or generalization in patients, and no correlation with impairment was noted. The healthy individuals performed better than patients on bimanual motor skill learning, but generalization was similar in both groups. Conclusions. A short motor skill learning session with a robotic device resulted in the retention and generalization of a complex skill involving bimanual cooperation. The tDCS strategy that would best enhance bimanual motor skill learning after stroke remains unknown.